EDUKASI KESEHATAN DAN PENGOLAHAN OBAT TRADISIONAL UNTUK PENINGKATAN IMUNITAS PADA MASA PANDEMI DI JORONG BANSA KECAMATAN KAMANG MAGEK KABUPATEN AGAM - Mulyanti Roberto Muliantino; Yuanita Ananda; Rika Sarfika (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2021)
Community empowerment was one effort in overcoming the spreading of Covid-19 in West Sumatera. West Sumatra has various types of community components that can be empowered, one of which is the PKK. Along with social restrictions that are too long and the circulation of false news about Covid-19 in the media, the implementation of the Covid-19 prevention health protocol is decreasing. Training and education of PKK members are strategy in solving the lack of knowledge of Covid-19, the low of self-management of communities in carrying out health protocols, and the community’s inability to take advantaged of the availability of natural ingredient of medicinal plants in their yard. The aim of these activities was to improve the knowledge of PKK Bansa’s members in increasing self-management in Covid-19 prevention and traditional medicine skill. The methods in this program were structure education and skill training for 25 members of PKK in Bansa. We used module, video demonstration and leaflet in this education and training program. Pre and post-test were held to evaluate the knowledge of participants. The result showed there was an increasing knowledge of participants before and after education and training from 34,84 to 41,4. Members of PKK can re-demonstration of making traditional medicine from ginger and turmeric to increase immunity during Covid-19 pandemic. The empowerment activity was effective and continuously way in elaborative and improving community’s participation in controlling the spreading of Covid-19.